Stock Selection, Style Rotation, and Risk - André Lucas; Ronald van Dijk; Teun Kloek (Tinbergen Institute, 2001)
Using US data from June 1984 to July 1999, we show that the impact of firm-specificcharacteristics like size and book-to-price on future excess stock returns varies considerably overtime. The impact can be either positive or negative at different times. This time variation ispartially predictable. We investigate whether the partial predictability signals security mispricing orrisk compensation by formulating alternative modeling strategies. The strategies are comparedempirically, In particular, we allow for a state-dependent choice of investment styles rather than aonce-and-for-all choice for a particular style, for example based on high book-to-price ratios orsmall market cap values. Using alternative ways to correct for risk, we find significant and robustexcess returns to style rotating investment strategies. Business cycle oriented approaches exhibitthe best overall performance. Purely statistical models for style rotation or fixed investment stylesreveal less robust behavior.
Keywords: 330; investment style; time-varying parameters; risk compensation; business cycles; Portfolio-Management; Kapitalanlage; Risiko; Zeitreihenanalyse; Konjunktur; USA